The Role Of Peer Assessment Model With A Web Platform In Participation And Learning Achievement Of Students - None Tuo Liu; None Sirirat Petsangsri; None Thanin Ratanaolarn; None Rongrong Guo (My University, 2023)
Technological innovations have led to the widespread use of web-based peer evaluation as an alternative formative assessment strategy. This assessment method has significant potential benefits for the education of the student population (Chien, Hwang, & Jong, 2020). A web-based peer evaluation system and a method for team improvement were developed in order to allow the rapid administration of the assessment, stimulate the provision of quality feedback, and construct effective team operations (Friedrich, 2019). However, very few teachers really put into practice peer evaluations that are completely anonymous. When implementing web-based peer assessment systems, both students and instructors will have obligations. The teachers often have a considerable impact on the outcomes of the usual classroom assessments (Liu, Li, & Zhang, 2017). The finding of this study suggests that there is a wider gap between the evaluations that males and females have of themselves based on their own self-assessments and the evaluations that the lecturer has of them based on their own evaluations. One of the many possible explanations for this phenomenon is that individuals often have a more favourable perception of their own intellect than females. The aim of this article is to provide evidence on the role of the Peer Assessment Model with A Web Platform in participation and learning. A total of fifty reputable publications were searched out; however, only five were proved to have a high level of authenticity and relevancy with the topic.
Keywords: Peer Assessment; Peer tutor; Educational Technology and Assessment